Menganalisa Hubungan Undang-Undang Cipta Kerja Dengan Kesejahteraan Karyawan - Dian Sudiantini; Sonya Febrina Narwastu Ambarita; Suhartini Suhartini; Widya Ananda; Zalendra Zalendra (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The Ciptaker Law functions to increase investment and create new jobs, but is controversial because of workers' rights. Analysis of the relationship between the Ciptaker Law and employee welfare needs to pay attention to the concept of Competency-Based Employment, which allows companies to appoint and terminate employment based on employee capabilities and performance. However, this threatens the rights of employees, especially regarding termination and wages. The Ciptaker Law also expands the types of work for foreign workers in Indonesia. Even though it can increase investment and create jobs, the Ciptaker Law has the potential to reduce employee wages and make it easier for companies to terminate employment. The implementation of the Ciptaker Law needs to be closely monitored and evaluate especially in terms of protecting employee rights so that this Law can improve welfare and decent employment opportunities. Sorry, please add the text you want shortened. Thank You.